Design of Ruangwakaf Application Business Model using Lean Canvas - Divanti Syaharani; Farda Hasun; Praptiwi Lestiyawati (International Journal of Innovation in Enterprise System, 2024)
Islamic boarding schools or pesantrens are places to learn about Islam that are spread throughoutIndonesia. The community empowerment function of pesantren in economic terms still requiresfurther development. One source of the problem is the difficulty in building business units, includingin the fulfilment of production facilities due to lack of capital, so they need support from the society.However, access to information related to the need for production facilities in pesantrens is not wellreached by society. So, the solution that can be offered is to develop waqf application as a liaisonbetween Islamic boarding schools and Indonesian society. The development of this applicationrequires a business model design. This research aims to design the business model of a productionfacilities waqf application named Ruangwakaf using lean canvas. The data needed is secondary datacollected from literature studies. After the data is collected, the next step is designing a businessmodel, and then doing logical verification. To proceed with the validation process, the applicationmock-up is designed, and then is used for the problem and solution validation process. The validationprocess is carried out by interviewing early adopters. The result of this research is a lean canvasbusiness model for the Ruangwakaf application. The unique value proposition offered to pesantren isone step to obtain capital assistance for production facilities and to the society is the easiest step towaqf. The solution provided in this application consists of five main features, those are RwWakaf,RwMart, RwStudy, RwConsult, and RwReport.